Buccal Pedicle Flap Combined With Porcine Collagen Matrix: A Follow‐Up of 2 Years on 40 Consecutive Cases. Issue 2 (23rd April 2021) - Tabanella, Giorgio
Abstract : Introduction: A thick peri‐implant mucosa is of importance to prevent recession, color alterations, bone remodeling and promote "creeping attachment." A volume stable porcine cross‐linked collagen matrix has been recently introduced for soft tissue regeneration and volume maintenance. The aim of this study was to investigate peri‐implant soft tissue healing and stability on 40 consecutive patients treated with buccal pedicle flap combined with the use of the collagen matrix. Case Series: The buccal pedicle flap combined with a volume stable collagen matrix was executed at second stage surgery. The average initial mucosa thickness was 1.32 mm whereas the average band of keratinized mucosa was 1.65 mm and the height 1.3 mm. Four months after surgical procedure and before delivering the final restoration, the peri‐implant soft tissue measurements were significantly increased: the average band of keratinized mucosa was 5.10 mm, the mucosa thickness was 3.27 mm, and the mucosa height was 3.32 mm. After 2 years of follow‐up, the superimposition of 3D models described an overall volumetric stability of the augmented mucosa with no signs of soft tissue collapse. Conclusion: The proposed modified buccal pedicle flap was demonstrated to perform well in terms of decreased morbidity, maintenance of blood supply, stabilization of the pedicle, superior haemostasis, and speed of treatment. No significant variations of the keratinized tissue were registered when the buccal pedicle flap was executed in conjunction with the collagen matrix that however provided color match with the surrounding tissue as well as an increased mucosa thickness.